2023
DOI: 10.3390/cancers15061691
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 Study to Evaluate the Safety of Reducing the Prophylactic Dose of Dexamethasone around Docetaxel Infusion in Patients with Prostate and Breast Cancer

Abstract: Background: There is little evidence that supports the registered high dose of dexamethasone used around docetaxel. However, this high dose is associated with considerable side effects. This study evaluates the feasibility of reducing the prophylactic oral dosage of dexamethasone around docetaxel infusion. Patients and methods: Eligible patients had a histologically confirmed diagnosis of prostate or breast cancer and had received at least three cycles of docetaxel as monotherapy or combination therapy. Prophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
1
1
Order By: Relevance
“…However, docetaxel and DEX administration methods (particularly DEX initiation date and administration duration) in the present study were different from those of previous studies. Specifically, docetaxel dose for breast cancer treatment in a prospective phase I study (100 mg/m 2 ) was higher than ours although their incidence of all-grade DIFR was lower 10 . A previous study reported that Japanese patients are more susceptible to docetaxel-induced toxicities 13 .…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…However, docetaxel and DEX administration methods (particularly DEX initiation date and administration duration) in the present study were different from those of previous studies. Specifically, docetaxel dose for breast cancer treatment in a prospective phase I study (100 mg/m 2 ) was higher than ours although their incidence of all-grade DIFR was lower 10 . A previous study reported that Japanese patients are more susceptible to docetaxel-induced toxicities 13 .…”
Section: Discussioncontrasting
confidence: 63%
“…To our knowledge, this is the first study to show that high-dose DEX prophylaxis attenuates DIFR. In contrast, previous reports suggested the possibility of reducing DEX dosage in docetaxel-containing treatment 10 12 . However, docetaxel and DEX administration methods (particularly DEX initiation date and administration duration) in the present study were different from those of previous studies.…”
Section: Discussionmentioning
confidence: 72%